Analisis Prediksi Penjualan Produk PT. Joenoes Ikamulya Menggunakan 4 Metode Peramalan Time Series - Wiharja, Andry Fernandus; Ningrum, Harini Fajar (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
The need of information is important in the strict of business competition. The quality and result of data information which have been processed affects the strategy and the succeeded in the future. Joenoes Ikamulya is a company concerns in selling product and it use the selling data to be transformed into useful information for the company itself. By counting the forecasting with several forecasting time series method and the error in each method, it is expected that the company could have information and the best result in the forecasting. The results from prediction system were made by 4 forecasting time series method, they are NaÃ¯ve Approach Method, Single Moving Average Method (with n = 1, 2, 3, 4, 5), Weighted Moving Average Method, Exponential Smoothing Method (with Î± = 0.1, 0.5, 0.9), and Trend Projection Method. The result from forecasting chosen from Weight Moving Average method is used as selling product prediction D Boday Wash and Evany, however, the result from Trend Projection method is used as selling profuct prediction for Aganol, Ligent, dan Porstex.